Genome-wide identification, expression and functional analysis of sugar transporters in sorghum (Sorghum bicolor L.) - Qian-lin XIAO; Zhen LI; Ya-yun WANG; Xian-bin HOU; Xi-mei WEI; Xiao ZHAO; Lei HUANG; Yan-jun GUO; Zhi-zhai LIU (Journal of Integrative Agriculture, 2022)
Sugar transporters are essential for osmotic process regulation, various signaling pathways and plant growth and development. Currently, few studies are available on the function of sugar transporters in sorghum (Sorghum bicolor L.). In this study, we performed a genome-wide survey of sugar transporters in sorghum. In total, 98 sorghum sugar transporters (SSTs) were identified via BLASTP. These SSTs were classified into three families based on the phylogenetic and conserved domain analysis, including six sucrose transporters (SUTs), 23 sugars will eventually be exported transporters (SWEETs), and 69 monosaccharide transporters (MSTs). The sorghum MSTs were further divided into seven subfamilies, including 24 STPs, 23 PLTs, two VGTs, four INTs, three pGlcT/SBG1s, five TMTs, and eight ERDs. Chromosomal localization of the SST genes showed that they were randomly distributed on 10 chromosomes, and substantial clustering was evident on the specific chromosomes. Twenty-seven SST genes from the families of SWEET, ERD, STP, and PLT were found to cluster in eight tandem repeat event regions. In total, 22 SSTs comprising 11 paralogous pairs and accounting for 22.4% of all the genes were located on the duplicated blocks. The different subfamilies of SST proteins possessed the same conserved domain, but there were some differences in features of the motif and transmembrane helices (TMH). The publicly-accessible RNA-sequencing data and real-time PCR revealed that the SST genes exhibited distinctive tissue specific patterns. Functional studies showed that seven SSTs were mainly located on the cell membrane and membrane organelles, and 14 of the SSTs could transport different types of monosaccharides in yeast. These findings will help us to further elucidate their roles in the sorghum sugar transport and sugar signaling pathways.